Prevalence of Cryptosporidium infection and associated risk factors in ruminants in Gauteng Province, South Africa - Marufu, Munyaradzi Christopher (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2024.